136 Spontaneous Breathing Patterns of Transitioning Preterm Infants in the Delivery Room (DR) and Interactions with Manual Positive Pressure Ventilation. (October 2012) - Schmölzer, G; Kaufman, J; Kamlin, O; Davis, P
Abstract : Background: Positive pressure ventilation (PPV) remains the cornerstone of respiratory support after birth. Effectiveness of PPV in the DR may be compromised by leak, obstruction and inappropriate tidal volume (VT ) delivery. Aim: Describe leak, obstruction and VT during spontaneous breathing amongst preterm infants transitioning in the DR and interaction of these breaths with mask ventilation. Methods: Patients were enrolled from the control arm of a randomised trial investigating the use of a respiratory function monitor (RFM) in the DR; infants < 32 weeks who were stabilised by paediatric trainees unaware of RFM data were included. During spontaneous breathing on mask continuous positive airway pressure (CPAP) and the delivery of PPV, airway pressures, gas flow and VT were recorded. Data were analysed by breath type. Results: In 29 infants, a total of 3864 inflations (mechanical) and inspirations (infant breaths) were analysed (Table 1 ). Overall mask leak was highest during spontaneous inspirations occurring between manual inflations and those during CPAP. The average VT was highest during combined inspiration and inflation. Conclusion: Preterm infants are active participants in stabilisation in the DR. VT and mask leak vary depending on the interaction between the infant's breathing efforts and the inflations provided by the resuscitator.